2013
DOI: 10.1080/1068316x.2013.793334
|View full text |Cite
|
Sign up to set email alerts
|

Are children less reliable at making visual identifications than adults? A review

Abstract: The current paper reviews research that has investigated developmental differences in lineup identification. A wealth of studies have shown that children can be as accurate as adults when making a correct identification from a target present lineup (TP), however children are more inclined to choose and thereby make a false identification from a target absent (TA) lineup, as compared to adults. The literature reviewed, suggests that the disparity between children's and adult's performances on TA lineups is due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
1
17
1
Order By: Relevance
“…Researchers most often report that while children do not differ from adults on target present lineups, they perform less accurately than adults on target absent lineups (for reviews see, Havard, 2013;Pozzulo, 2007;Pozzulo & Lindsay, 1998). It is not clear, however, whether these findings can be accounted for by the late maturation hypothesis, because previous analyses have not properly taken into account developmental differences in response bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers most often report that while children do not differ from adults on target present lineups, they perform less accurately than adults on target absent lineups (for reviews see, Havard, 2013;Pozzulo, 2007;Pozzulo & Lindsay, 1998). It is not clear, however, whether these findings can be accounted for by the late maturation hypothesis, because previous analyses have not properly taken into account developmental differences in response bias.…”
Section: Discussionmentioning
confidence: 99%
“…a lineup containing only innocent persons), children are significantly more likely than adults to incorrectly identify someone as the perpetrator (Beal, Schmitt, & Dekle, 1995;Davies, 1996;Dekle, Beal, Elliott, & Huneycutt, 1996;Parker & Carranza, 1989;Parker & Ryan, 1993;Pozzulo & Balfour, 2006;Pozzulo & Dempsey, 2006). By adolescence (10-14 years), some research indicates that identification accuracy in target-absent lineups reaches adult levels Pozzulo & Warren, 2003, Experiment 2; for reviews, see, Havard, 2013: Pozzulo, 2007Pozzulo & Lindsay, 1998).…”
Section: Receiver Operating Characteristic Analysis Of Age-related Chmentioning
confidence: 99%
“…Research has also found a similar pattern for child witnesses, who are more likely to make false identifications 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 3 from TA lineups, but can be as accurate as young adults for TP lineups (for a review of the literature on child witnesses please see Havard, 2014).…”
Section: Older Adult Witnessesmentioning
confidence: 99%
“…Over the last few years, more research has begun to examine the accuracy of older adult witnesses, (see for a review and Erickson, Lampinen & Moore, 2015, for a meta-analysis) and has explored methods that may improve older adults' eyewitness accuracy (Wilcock & Bull, 2010;2014). The aim of the current study was to investigate whether a technique previously used to improve children's lineup identifications (Havard & Memon, 2013), namely the use of a silhouette (mystery man) in a lineup would also increase the reliability of older adults' identification decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Using recognition memory paradigm (learning a set of faces followed by an old/new recognition test using the previously studies faces mixed with an equal set of distractors [1], children under the age of ten were found to have lower rates of hits (the correct identification of previously-seen faces) and correct rejections (the rejection of previously-unseen faces) than older individuals [2]. In contrast, using the eyewitness identification methodology (seeing a target person through a video or live staged crime followed by an identification test using two target-present and target-absent lineups [3], children over five years of age were found to produce a hit rate that is comparable to adults [4] but older children still produce lower correct rejections [5].…”
mentioning
confidence: 97%